شكل الهيكل التمويلي المصرفي ودوره في تقليل حالات الفشل المالي وفقاً لنموذج SHERROD للفشل المالي: دراسة تطبيقية في عينة من المصارف التجارية الخاصة العاملة في العراق للمدة (2004-2020 (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This study aims to re and financial performance, ie (knowing the impact analyze the relationship between the financial structu of the financial structure on financial performance) in the Iraqi privatecommercial banks listed in the Iraq Stock Exchange. The importance of the study stems from theprimary goal pursued by commercial banks, which is to maximize their profitability and raise their financial performance, and through financial decisions related to choosing the optimal financial structure composition. A sample of (10) commercial banks registered in the Iraq Stock Exchange for the period from (2004- 220) To measure this effect or the relationship between the financial structure as an independent variable, the following financial ratios were used: (The financial leverage ratios are represented by: the ratio of total debts to equity, by the ratio of total debts to total assets, the ratio of total deposits to total equity, and a ratio representing Ownership structure represented by: the ratio of owned capital to total assets , the ratio of owned capital / total deposits, owned capital weighted  assets and between financial performance, so it was measured through: liquidity ratio, profitability ratio, and credit risk ratios The study concluded, according to the results of the financial analysis ratios, that the financial structure in the Iraqi banks, the study sample, and during the period under study depends on the financial leverage represented by the total debts to the total assets by a greater percentage in raising the financial performance compared to the internal funding sources. The study also concluded that liquidity in Iraqi banks constituted the largest proportion compared to profitability as a result of these banks retaining a large percentage of deposits or capital without investment, based on the decision of the Central Bank Board of Directors, which stipulates the adoption of a liquidity ratio of not less than 80% in order to raise the capacity of banks To meet its obligations in the short and medium term, and that the percentage of profits that were achieved from the main banking activity represented by credit facilities, especially granting loans, constituted a limited and small percentage of the total profit, while these banks relied in achieving their profits mainly on their other activities represented by the currency auction In addition to investments in stocks, bonds, clearing houses, leases, and others.)